Fine mapping of chromosome 15q25 implicates ZNF592 in neurosarcoidosis patients - Lareau, Caleb A (Ann Clin Transl Neurol, 2015)
Neurosarcoidosis is a clinical subtype of sarcoidosis characterized by the presence of granulomas in the nervous system. Here, we report a highly significant association with a variant (rs75652600, P = 3.12 × 10(−8), odds ratios = 4.34) within a zinc finger gene, ZNF592, from an imputation-based fine-mapping study of the chromosomal region 15q25 in African-Americans with neurosarcoidosis. We validate the association with ZNF592, a gene previously shown to cause cerebellar ataxia, in a cohort of European-Americans with neurosarcoidosis by uncovering low-frequency variants with a similar risk effect size (chr15:85309284, P = 0.0021, odds ratios = 5.36).